How to prove this? If \[a + b + c = 0\], then show that, \[{a^2} - bc = {b^2} - ca = {c^2} - ab\]
Answer
Verified
442.8k+ views
Hint:
Here, we will use the given condition to find one variable in terms of the other two variables. Then we will take each expression of the equation and substitute the obtained variable in each expression. We will simplify it further and prove that the given statement is true.
Formula Used:
The square of the sum of the numbers is given by an algebraic identity \[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\]
Complete step by step solution:
The given equation is \[a + b + c = 0\].
Now, by rewriting the equation, we get
\[ \Rightarrow c = - \left( {a + b} \right)\] ………………………………………………………………….\[\left( 1 \right)\]
Now, we will prove the given condition \[{a^2} - bc = {b^2} - ca = {c^2} - ab\] one by one and we will prove that all the three given conditions leads to the same result.
First, we will find the result of the first expression, \[{a^2} - bc\], by substituting equation \[\left( 1 \right)\]. Therefore, we get
\[{a^2} - bc = {a^2} - b\left( { - \left( {a + b} \right)} \right)\]
We know that the product of two negative integers is a positive integer, so we get
\[ \Rightarrow {a^2} - bc = {a^2} + b\left( {a + b} \right)\]
By multiplying the terms, we get
\[ \Rightarrow {a^2} - bc = {a^2} + {b^2} + ab\] ………………………………………………….\[\left( 2 \right)\]
Now, we will find the result of the second expression \[{b^2} - ca\] by substituting equation \[\left( 1 \right)\].
\[{b^2} - ca = {b^2} - \left( { - \left( {a + b} \right)} \right)a\]
We know that the product of two negative integers is a positive integer, so we get
\[ \Rightarrow {b^2} - ca = {b^2} + \left( {a + b} \right)a\]
Multiplying the terms, we get
\[ \Rightarrow {b^2} - ca = {b^2} + {a^2} + ab\] ………………………………………………….\[\left( 3 \right)\]
Now, we will find the result of the third expression \[{c^2} - ca\] by substituting equation\[\left( 1 \right)\].
\[{c^2} - ca = {\left( { - \left( {a + b} \right)} \right)^2} - ca\]
We know that the product of two negative integers is a positive integer.
Now, by using an algebraic identity \[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\], we get
\[ \Rightarrow {c^2} - ab = {a^2} + {b^2} + 2ab - ab\]
Simplifying the expression, we get
\[ \Rightarrow {c^2} - ab = {a^2} + {b^2} + ab\] ………………………………………………….\[\left( 4 \right)\]
So, we get \[{a^2} - bc = {b^2} - ca = {c^2} - ab = {a^2} + {b^2} + ab\]
Therefore, \[{a^2} - bc = {b^2} - ca = {c^2} - ab\] is proved true when \[a + b + c = 0\].
Note:
We know that the given expression is an algebraic expression. An algebraic expression is defined as an expression with the combination of variables, constants and operators. We can also find the variables \[a\] and \[b\] in terms of the other variable by using the given condition. So, we get \[a = - \left( {b + c} \right)\] and \[b = - \left( {a + c} \right)\]. By substituting these variables in the given expression we will prove the same results which are equal for all the three expressions.
Here, we will use the given condition to find one variable in terms of the other two variables. Then we will take each expression of the equation and substitute the obtained variable in each expression. We will simplify it further and prove that the given statement is true.
Formula Used:
The square of the sum of the numbers is given by an algebraic identity \[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\]
Complete step by step solution:
The given equation is \[a + b + c = 0\].
Now, by rewriting the equation, we get
\[ \Rightarrow c = - \left( {a + b} \right)\] ………………………………………………………………….\[\left( 1 \right)\]
Now, we will prove the given condition \[{a^2} - bc = {b^2} - ca = {c^2} - ab\] one by one and we will prove that all the three given conditions leads to the same result.
First, we will find the result of the first expression, \[{a^2} - bc\], by substituting equation \[\left( 1 \right)\]. Therefore, we get
\[{a^2} - bc = {a^2} - b\left( { - \left( {a + b} \right)} \right)\]
We know that the product of two negative integers is a positive integer, so we get
\[ \Rightarrow {a^2} - bc = {a^2} + b\left( {a + b} \right)\]
By multiplying the terms, we get
\[ \Rightarrow {a^2} - bc = {a^2} + {b^2} + ab\] ………………………………………………….\[\left( 2 \right)\]
Now, we will find the result of the second expression \[{b^2} - ca\] by substituting equation \[\left( 1 \right)\].
\[{b^2} - ca = {b^2} - \left( { - \left( {a + b} \right)} \right)a\]
We know that the product of two negative integers is a positive integer, so we get
\[ \Rightarrow {b^2} - ca = {b^2} + \left( {a + b} \right)a\]
Multiplying the terms, we get
\[ \Rightarrow {b^2} - ca = {b^2} + {a^2} + ab\] ………………………………………………….\[\left( 3 \right)\]
Now, we will find the result of the third expression \[{c^2} - ca\] by substituting equation\[\left( 1 \right)\].
\[{c^2} - ca = {\left( { - \left( {a + b} \right)} \right)^2} - ca\]
We know that the product of two negative integers is a positive integer.
Now, by using an algebraic identity \[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\], we get
\[ \Rightarrow {c^2} - ab = {a^2} + {b^2} + 2ab - ab\]
Simplifying the expression, we get
\[ \Rightarrow {c^2} - ab = {a^2} + {b^2} + ab\] ………………………………………………….\[\left( 4 \right)\]
So, we get \[{a^2} - bc = {b^2} - ca = {c^2} - ab = {a^2} + {b^2} + ab\]
Therefore, \[{a^2} - bc = {b^2} - ca = {c^2} - ab\] is proved true when \[a + b + c = 0\].
Note:
We know that the given expression is an algebraic expression. An algebraic expression is defined as an expression with the combination of variables, constants and operators. We can also find the variables \[a\] and \[b\] in terms of the other variable by using the given condition. So, we get \[a = - \left( {b + c} \right)\] and \[b = - \left( {a + c} \right)\]. By substituting these variables in the given expression we will prove the same results which are equal for all the three expressions.
Recently Updated Pages
Master Class 9 General Knowledge: Engaging Questions & Answers for Success
Master Class 9 English: Engaging Questions & Answers for Success
Master Class 9 Science: Engaging Questions & Answers for Success
Master Class 9 Social Science: Engaging Questions & Answers for Success
Master Class 9 Maths: Engaging Questions & Answers for Success
Class 9 Question and Answer - Your Ultimate Solutions Guide
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.